2008
DOI: 10.29310/wp.2008.12
|View full text |Cite
|
Sign up to set email alerts
|

Labour Productivity in Auckland Firms

Abstract: This paper examines labour productivity in Auckland, New Zealand's largest city, using microdata from Statistics New Zealand's Prototype Longitudinal Business Database. It documents a sizeable productivity premium in Auckland, around half of which is due to industry composition. There is a cross sectional correlation between productivity and employment density, reflecting differences in both physical productivity and prices. This correlation is evident both within Auckland, and comparing Auckland with other ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 10 publications
0
28
1
Order By: Relevance
“…The presence of positive agglomeration elasticities found in New Zealand and elsewhere (see Maré, 2008;Maré and Graham, 2009) indicates that increasing returns to scale may be present in relation to some infrastructure investments. The possibility of such increasing returns needs to be accounted for in ex ante assessments of the benefits flowing from new infrastructure investments.…”
Section: Arthur Grimesmentioning
confidence: 94%
“…The presence of positive agglomeration elasticities found in New Zealand and elsewhere (see Maré, 2008;Maré and Graham, 2009) indicates that increasing returns to scale may be present in relation to some infrastructure investments. The possibility of such increasing returns needs to be accounted for in ex ante assessments of the benefits flowing from new infrastructure investments.…”
Section: Arthur Grimesmentioning
confidence: 94%
“…Nonetheless, a key aspect of the relationship 11 Previous studies of Auckland have also shown a higher density of population and employment closer to the centre of Auckland. (Maré, 2008;Williamson et al, 2008) between density and price is again its heterogeneity. Figure 7 indicates that a large range of population densities exist at all prices.…”
Section: 1mentioning
confidence: 99%
“…The programme has included analyses of: transport infrastructure (Grimes, 2007;Grimes and Liang, 2010;Grimes and Young, 2010a;Fabling, Grimes and Sanderson, 2010); telecommunications infrastructure (Grimes, Ren and Stevens, 2009;Grimes, 2010b;Howell and Grimes, 2010); water infrastructure (Grimes and Aitken, 2008); social infrastructure (Roskruge et al, 2010); primary processing infrastructure (Grimes and Young, 2009); impacts of legal (planning) constraints on infrastructure outcomes (Grimes and Liang, 2009); infrastructure impacts on national and city productivity (Maré, 2008;Maré and Graham, 2009); and effects of local authority infrastructure investments on economic outcomes (Cochrane et al, 2010). Analyses of funding mechanisms (Coleman andGrimes, 2010a and2010b) and theoretical issues involved in ex ante assessments of infrastructure (Grimes, 2009a(Grimes, , 2010a have addressed additional conceptual issues.…”
Section: Infrastructurementioning
confidence: 99%
“…The 'agglomeration' relationship between infrastructure impacts and urban status (implied by the primary processing study) is emphasised in two analyses of firm productivity and employment density (Maré, 2008;Maré and Graham, 2009). Large urban areas tend to have greater infrastructure requirements and greater employment density than smaller areas.…”
Section: Local Social and Economic Infrastructurementioning
confidence: 99%
See 1 more Smart Citation